CompTIA Security+ Certification SY0-601 the Total Course - Seminars, Total; Meyers, Mike; Lachance, Daniel (Packt Publishing, 2021)
Your guide to prepare and clear the CompTIA Security+ Certification SY0-601 exam. About This Video Understand the various risk management concepts Learn the various cryptographic methods used to protect the critical keys in cryptography Understand the Diffie-Hellman key exchange agreement and methods In Detail Excel the CompTIA Security+ Certification SY0-601 exam by taking this course, which deep dives into the various concepts of risk management and various kinds of risk involved, and the various security standards such as PCI DSS and the Cloud Controls Matrix (CCM) define what types of security controls to put in place to mitigate risk both on-premises and in the cloud. Learn about data protection and the various cryptographic methods used to protect the critical keys in cryptography that keep communication secure. The course also reviews different types of certificates including web, email, code-signing, machine/computer, and user. Explore the 3 As--authentication, authorization, and accounting/auditing, which play a big role in IT security. Tracking activity through auditing provides accountability for access to resources such as files on a file server or database rows. Learn about securing dedicated systems using IoT. IoT devices are function-specific and can communicate over the Internet. Examples include environmental control devices, medical devices, and video surveillance systems. This episode also covers the Zigbee smart home automation protocol. Wrap up the course by understanding data backup; backing up data provides availability in the event of data deletion, corruption, or encryption through ransomware. This episode discusses backup settings such as compression and encryption, as well as full, differential, and incremental backup types.
Online resource; Title from title screen (viewed July 30, 2021)
Keywords: Streaming video; Internet videos; Vidéo en continu; Vidéos sur Internet; streaming video; Electronic videos